Analisis Implementasi Etika Bisnis, Strategi Manajemen, dan Efisiensi Pengolahan Pada UMKM Wanita Singkong Jaya Terhadap Sistem Sosial Ekonomi di Desa Sukowilangun - Dinanda Primanagari; M. Cholid Mawardi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
In this era especially during the pandemic, villages must be smarter in building the economy and make the village an independent village which must have micro, small and medium (UMKM) businesses that are able to help the village economy. In business, especially small and medium (UMKM) enterprises, micro must pay attention to business ethics, management strategies and good and correct processing efficiency because this is also one of the reason for the cracking of an business, from the results of the study, it was found that several problems were caused by a lack of understanding related to business ethics and their solutions so that this research was to meet the needs of UMKM actors in understanding and implementing business ethics, management strategies and processing efficiency.Keywords : UMKM, business ethics, management strategies and processing efficiency